Modified asphalt-based hard carbon negative electrode material and preparation method thereof
By pulverizing, preoxidizing and gas-phase coating, a modified asphalt-based hard carbon anode material with amorphous carbon coat is formed, which solves the problems of poor electrochemical performance and low carbonization efficiency of sodium ion battery anode materials, and achieves the effects of high energy density and good cycle performance.
Patent Information
- Application Number
- CN202510086362.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-03-14
AI Technical Summary
The electrochemical performance of existing sodium ion battery negative electrode materials is poor, and the carbonization efficiency of bituminous hard carbon is low, resulting in increased costs.
By pulverizing and preoxidizing the asphalt, the carbon source gas and oxidized asphalt were mixed and reacted by gas-phase coating to form a hard carbon precursor, and calcined and carbonized at high temperature under an inert atmosphere to obtain a modified asphalt-based hard carbon anode material coated with amorphous carbon.
The carbonization efficiency and electrochemical performance of asphalt-based hard carbon are improved, and the high energy density and good cycle performance of the negative electrode material of sodium ion battery are achieved. At the same time, the process equipment is simplified and easy to industrialize.
Smart Images

Figure CN119612498A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a modified asphalt-based hard carbon negative electrode material and a preparation method thereof. Background Art
[0002] With the continuous progress of social development, the new energy industry is also developing rapidly. The scarcity of lithium resources has led to the risk of increasing costs for mainstream lithium-ion batteries. Therefore, developing applications with more cost advantages is more conducive to the development of the new energy industry. Sodium-ion batteries are the most likely energy storage application to replace lithium-ion batteries in the future due to their rich resources, wide distribution and low cost.
[0003] In the direction of the negative electrode of sodium-ion batteries, since the radius of sodium atoms is larger than that of lithium atoms, the graphite negative electrode suitable for lithium-ion batteries cannot be used in sodium-ion batteries because it cannot embed sodium. Hard carbon is generally considered to be the most mainstream choice for the negative electrode of sodium-ion batteries due to its advantages such as high sodium storage capacity, small volume deformation after embedding sodium, good conductivity, low redox potential and environmental friendliness. The precursor materials used in hard carbon are mainly biomass and resins. However, the carbonization yield of biomass-based hard carbon is low, and the cost of the synthesis process of resin-based hard carbon is too high. In the long run, both are not conducive to sodium-ion batteries to better play the low-cost advantage. Asphalt, as a petroleum by-product, has a low price and a high carbonization yield. Therefore, using asphalt as a precursor to prepare asphalt-based hard carbon is an ideal route for the negative electrode of sodium-ion batteries.
[0004] However, the material obtained by direct carbonization of asphalt has very poor electrochemical performance as the negative electrode of sodium ion battery. This is because melting occurs during direct carbonization of asphalt, the degree of graphitization increases, and a highly ordered structure is formed to finally obtain a soft carbon material. Therefore, the asphalt precursor needs to be modified and coated to improve the electrochemical performance of the material. Patent document CN115744871A discloses a composite hard carbon material formed by using bagasse as a substrate and performing structural regulation and surface defect repair through asphalt coating. The material properties are improved, but the low carbonization yield of bagasse-based hard carbon increases the cost. Therefore, how to find a suitable method to improve the capacity and carbonization yield of asphalt-based hard carbon is a challenge faced by current work. Summary of the invention
[0005] One of the purposes of the present invention is to provide a method for preparing a modified asphalt-based hard carbon negative electrode material to solve the problem of poor asphalt carbonization efficiency;
[0006] The second object of the present invention is to provide a modified asphalt-based hard carbon negative electrode material prepared by the preparation method to solve the problem of poor electrochemical performance of the negative electrode of the sodium ion battery;
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] In a first aspect, a method for preparing a modified asphalt-based hard carbon negative electrode material comprises the following steps:
[0009] S1. The asphalt is crushed to obtain crushed asphalt, and pre-oxidized in an air atmosphere to obtain oxidized asphalt;
[0010] S2. A gas-phase coating method is used to react a mixed gas composed of a carbon source gas and an organic gas with an oxidized asphalt to obtain a hard carbon precursor;
[0011] S3. The hard carbon precursor is placed in an inert atmosphere for calcination and carbonization, and after cooling, a modified asphalt-based hard carbon negative electrode material is obtained.
[0012] As a further solution of the present invention, in S1, the asphalt includes any one of petroleum asphalt, coal asphalt, and natural asphalt, or a combination of several of them.
[0013] As a further solution of the present invention, in S1, the asphalt is crushed by a mechanical crusher, and the crushed asphalt is crushed by a mechanical crusher. 50 3-10μm.
[0014] As a further solution of the present invention, in S1, the pre-oxidation temperature is 300-500° C., and the pre-oxidation time is 3-10 h.
[0015] As a further solution of the present invention, in S2, the volume ratio of the carbon source gas to the organic gas is 6:(1-2).
[0016] As a further embodiment of the present invention, in S2, the organic gas is one or a mixture of two or more of methane, ethane and toluene.
[0017] As a further embodiment of the present invention, in S2, the mass ratio of the carbon source gas to the oxidized asphalt is (5-10):100;
[0018] And / or, the carbon source gas is propylene.
[0019] As a further solution of the present invention, in said S2, the coating temperature of the gas phase coating method is 700-900°C.
[0020] As a further solution of the present invention, in S3, the calcination temperature is 900-1500° C., and the calcination time is 2-5 hours.
[0021] As a further embodiment of the present invention, in S3, the inert gas is one or more of nitrogen, helium and argon.
[0022] In the second aspect, a modified asphalt-based hard carbon negative electrode material is prepared by the above-mentioned preparation method. When the negative electrode material is used as a negative electrode of a sodium ion battery, the reversible capacity reaches 298 mAh / g, and the first effect (first coulomb efficiency) is increased to 88%.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The present invention provides a method for preparing a modified asphalt-based hard carbon negative electrode material, wherein the asphalt is crushed and screened to obtain crushed asphalt with a small particle size; the crushed asphalt is pre-oxidized in an air atmosphere to obtain oxidized asphalt to improve the microstructure of the material; the carbon source gas and the oxidized asphalt are violently stirred and fully mixed by gas phase coating, so that the carbon source is deposited on the surface of the oxidized asphalt, and then the asphalt-based hard carbon material coated with amorphous carbon with high carbonization efficiency is obtained after high-temperature carbonization.
[0025] 2. The modified asphalt-based hard carbon negative electrode material prepared by the present invention has improved the surface pore structure through the asphalt-based hard carbon coated with amorphous carbon, and reduced the active sites of the material surface in contact with the electrolyte. Therefore, it can hinder a part of the irreversible sodium adsorption, inhibit the decomposition of the electrolyte, and reduce the occurrence of side reactions. It can be used as a negative electrode material for sodium ion batteries to obtain sodium ion batteries with high energy density and good cycle performance. In addition, the process of the present invention is short, the process equipment is simple, and it is easy to realize industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The present invention will be further described below in conjunction with the accompanying drawings.
[0027] Figure 1 This is a schematic diagram of the first charge and discharge of the modified asphalt-based hard carbon negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Example 1
[0030] This embodiment provides a method for preparing a modified asphalt-based hard carbon negative electrode material, comprising the following steps:
[0031] S1. The asphalt is crushed by a mechanical crusher, and after screening, the crushed asphalt with a particle size of 5 μm is obtained, and then pre-oxidized for 5 hours at a temperature of 350° C. in an air atmosphere to obtain oxidized asphalt;
[0032] S2. The oxidized asphalt is subjected to gas-phase coating treatment by fluidized bed CVD equipment, the oxidized asphalt is placed in a fluidized bed reactor, nitrogen is used as a carrier, a mixed gas consisting of a carbon source gas and an organic gas is introduced into the fluidized bed reactor, and the carbon source gas and the oxidized asphalt are violently stirred and fully mixed at a temperature of 800°C to achieve coating of the oxidized asphalt to obtain a hard carbon precursor material; wherein the carbon source gas is propylene, the organic gas is methane, the mass ratio of the oxidized asphalt to propylene is 15:1, and the volume ratio of propylene to methane is 4:1;
[0033] S3. After the hard carbon precursor is cooled to room temperature (25-30°C), it is placed in a nitrogen atmosphere and subjected to high-temperature calcination and carbonization at 1200°C for 2 hours. After cooling, an amorphous carbon-coated modified asphalt-based hard carbon negative electrode material is obtained.
[0034] Example 2
[0035] This embodiment provides a method for preparing a modified asphalt-based hard carbon negative electrode material, comprising the following steps:
[0036] S1. The asphalt is crushed by a mechanical crusher, and after screening, the crushed asphalt with a particle size of 5 μm is obtained, and then pre-oxidized for 5 hours at a temperature of 350° C. in an air atmosphere to obtain oxidized asphalt;
[0037] S2. The oxidized asphalt is subjected to gas-phase coating treatment by fluidized bed CVD equipment, the oxidized asphalt is placed in a fluidized bed reactor, nitrogen is used as a carrier, a mixed gas consisting of a carbon source gas and an organic gas is introduced into the fluidized bed reactor, and the carbon source gas and the oxidized asphalt are violently stirred and fully mixed at a temperature of 800°C to achieve coating of the oxidized asphalt and obtain a hard carbon precursor material; wherein the carbon source gas is propylene, the organic gas is methane, the mass ratio of the oxidized asphalt to propylene is 20:1, and the volume ratio of propylene to methane is 4:1;
[0038] S3. After the hard carbon precursor is cooled to room temperature, it is placed in a nitrogen atmosphere and subjected to high-temperature calcination and carbonization at 1200°C for 2 hours. After cooling, an amorphous carbon-coated modified asphalt-based hard carbon negative electrode material is obtained.
[0039] Example 3
[0040] This embodiment provides a method for preparing a modified asphalt-based hard carbon negative electrode material, comprising the following steps:
[0041] S1. The asphalt is crushed by a mechanical crusher, and after screening, the crushed asphalt with a particle size of 5 μm is obtained, and then pre-oxidized for 5 hours at a temperature of 350° C. in an air atmosphere to obtain oxidized asphalt;
[0042] S2. The oxidized asphalt is subjected to gas-phase coating treatment by fluidized bed CVD equipment, the oxidized asphalt is placed in a fluidized bed reactor, nitrogen is used as a carrier, a mixed gas consisting of a carbon source gas and an organic gas is introduced into the fluidized bed reactor, and the carbon source gas and the oxidized asphalt are violently stirred and fully mixed at a temperature of 800°C to achieve coating of the oxidized asphalt and obtain a hard carbon precursor material; wherein the carbon source gas is propylene, the organic gas is methane, the mass ratio of the oxidized asphalt to propylene is 10:1, and the volume ratio of propylene to methane is 4:1;
[0043] S3. After the hard carbon precursor is cooled to room temperature, it is placed in a nitrogen atmosphere and subjected to high-temperature calcination and carbonization at 1200°C for 2 hours. After cooling, an amorphous carbon-coated modified asphalt-based hard carbon negative electrode material is obtained.
[0044] Example 4
[0045] This embodiment provides a method for preparing a modified asphalt-based hard carbon negative electrode material, comprising the following steps:
[0046] S1. The asphalt is crushed by a mechanical crusher, and after screening, the crushed asphalt with a particle size of 5 μm is obtained, and then pre-oxidized for 5 hours at a temperature of 350° C. in an air atmosphere to obtain oxidized asphalt;
[0047] S2. The oxidized asphalt is subjected to gas-phase coating treatment by fluidized bed CVD equipment, the oxidized asphalt is placed in a fluidized bed reactor, nitrogen is used as a carrier, a mixed gas consisting of a carbon source gas and an organic gas is introduced into the fluidized bed reactor, and the carbon source gas and the oxidized asphalt are violently stirred and fully mixed at a temperature of 800°C to achieve coating of the oxidized asphalt and obtain a hard carbon precursor material; wherein the carbon source gas is propylene, the organic gas is methane, the mass ratio of the oxidized asphalt to propylene is 15:1, and the volume ratio of propylene to methane is 6:1;
[0048] S3. After the hard carbon precursor is cooled to room temperature, it is placed in a nitrogen atmosphere and subjected to high-temperature calcination and carbonization at 1200°C for 2 hours. After cooling, an amorphous carbon-coated modified asphalt-based hard carbon negative electrode material is obtained.
[0049] Example 5
[0050] This embodiment provides a method for preparing a modified asphalt-based hard carbon negative electrode material, comprising the following steps:
[0051] S1. The asphalt is crushed by a mechanical crusher, and after screening, the crushed asphalt with a particle size of 5 μm is obtained, and then pre-oxidized for 5 hours at a temperature of 350° C. in an air atmosphere to obtain oxidized asphalt;
[0052] S2. The oxidized asphalt is subjected to gas-phase coating treatment by fluidized bed CVD equipment, the oxidized asphalt is placed in a fluidized bed reactor, nitrogen is used as a carrier, a mixed gas consisting of a carbon source gas and an organic gas is introduced into the fluidized bed reactor, and the carbon source gas and the oxidized asphalt are violently stirred and fully mixed at a temperature of 800°C to achieve coating of the oxidized asphalt to obtain a hard carbon precursor material; wherein the carbon source gas is propylene, the organic gas is methane, the mass ratio of the oxidized asphalt to propylene is 15:1, and the volume ratio of propylene to methane is 3:1;
[0053] S3. After the hard carbon precursor is cooled to room temperature, it is placed in a nitrogen atmosphere and subjected to high-temperature calcination and carbonization at 1200°C for 2 hours. After cooling, an amorphous carbon-coated modified asphalt-based hard carbon negative electrode material is obtained.
[0054] Example 6
[0055] This embodiment provides a method for preparing a modified asphalt-based hard carbon negative electrode material, comprising the following steps:
[0056] S1. The asphalt is crushed by a mechanical crusher, and after screening, the crushed asphalt with a particle size of 5 μm is obtained, and then pre-oxidized for 5 hours at a temperature of 300° C. in an air atmosphere to obtain oxidized asphalt;
[0057] S2. The oxidized asphalt is subjected to gas-phase coating treatment by fluidized bed CVD equipment, the oxidized asphalt is placed in a fluidized bed reactor, nitrogen is used as a carrier, a mixed gas consisting of a carbon source gas and an organic gas is introduced into the fluidized bed reactor, and the carbon source gas and the oxidized asphalt are violently stirred and fully mixed at a temperature of 800°C to achieve coating of the oxidized asphalt to obtain a hard carbon precursor material; wherein the carbon source gas is propylene, the organic gas is methane, the mass ratio of the oxidized asphalt to propylene is 15:1, and the volume ratio of propylene to methane is 4:1;
[0058] S3. After the hard carbon precursor is cooled to room temperature, it is placed in a nitrogen atmosphere and subjected to high-temperature calcination and carbonization at 1200°C for 2 hours. After cooling, an amorphous carbon-coated modified asphalt-based hard carbon negative electrode material is obtained.
[0059] Example 7
[0060] This embodiment provides a method for preparing a modified asphalt-based hard carbon negative electrode material, comprising the following steps:
[0061] S1. The asphalt is crushed by a mechanical crusher, and after screening, the crushed asphalt with a particle size of 5 μm is obtained, and then pre-oxidized for 5 hours at a temperature of 450° C. in an air atmosphere to obtain oxidized asphalt;
[0062] S2. The oxidized asphalt is subjected to gas-phase coating treatment by fluidized bed CVD equipment, the oxidized asphalt is placed in a fluidized bed reactor, nitrogen is used as a carrier, a mixed gas consisting of a carbon source gas and an organic gas is introduced into the fluidized bed reactor, and the carbon source gas and the oxidized asphalt are violently stirred and fully mixed at a temperature of 800°C to achieve coating of the oxidized asphalt to obtain a hard carbon precursor material; wherein the carbon source gas is propylene, the organic gas is methane, the mass ratio of the oxidized asphalt to propylene is 15:1, and the volume ratio of propylene to methane is 4:1;
[0063] S3. After the hard carbon precursor is cooled to room temperature, it is placed in a nitrogen atmosphere and subjected to high-temperature calcination and carbonization at 1200°C for 2 hours. After cooling, an amorphous carbon-coated modified asphalt-based hard carbon negative electrode material is obtained.
[0064] Example 8
[0065] This embodiment provides a method for preparing a modified asphalt-based hard carbon negative electrode material, comprising the following steps:
[0066] S1. The asphalt is crushed by a mechanical crusher, and after screening, the crushed asphalt with a particle size of 5 μm is obtained, and then pre-oxidized for 5 hours at a temperature of 350° C. in an air atmosphere to obtain oxidized asphalt;
[0067] S2. The oxidized asphalt is subjected to gas-phase coating treatment by fluidized bed CVD equipment, the oxidized asphalt is placed in a fluidized bed reactor, nitrogen is used as a carrier, a mixed gas consisting of a carbon source gas and an organic gas is introduced into the fluidized bed reactor, and the carbon source gas and the oxidized asphalt are violently stirred and fully mixed at a temperature of 800°C to achieve coating of the oxidized asphalt to obtain a hard carbon precursor material; wherein the carbon source gas is propylene, the organic gas is methane, the mass ratio of the oxidized asphalt to propylene is 15:1, and the volume ratio of propylene to methane is 4:1;
[0068] S3. After the hard carbon precursor is cooled to room temperature, it is placed in a nitrogen atmosphere and subjected to high-temperature calcination and carbonization at 900°C for 2 hours. After cooling, an amorphous carbon-coated modified asphalt-based hard carbon negative electrode material is obtained.
[0069] Example 9
[0070] This embodiment provides a method for preparing a modified asphalt-based hard carbon negative electrode material, comprising the following steps:
[0071] S1. The asphalt is crushed by a mechanical crusher, and after screening, the crushed asphalt with a particle size of 5 μm is obtained, and then pre-oxidized for 5 hours at a temperature of 300° C. in an air atmosphere to obtain oxidized asphalt;
[0072] S2. The oxidized asphalt is subjected to gas-phase coating treatment by fluidized bed CVD equipment, the oxidized asphalt is placed in a fluidized bed reactor, nitrogen is used as a carrier, a mixed gas consisting of a carbon source gas and an organic gas is introduced into the fluidized bed reactor, and the carbon source gas and the oxidized asphalt are violently stirred and fully mixed at a temperature of 800°C to achieve coating of the oxidized asphalt to obtain a hard carbon precursor material; wherein the carbon source gas is propylene, the organic gas is methane, the mass ratio of the oxidized asphalt to propylene is 15:1, and the volume ratio of propylene to methane is 4:1;
[0073] S3. After the hard carbon precursor is cooled to room temperature, it is placed in a nitrogen atmosphere and subjected to high-temperature calcination and carbonization at 1500°C for 2 hours. After cooling, an amorphous carbon-coated modified asphalt-based hard carbon negative electrode material is obtained.
[0074] Comparative Example 1
[0075] This comparative example provides a method for preparing a pitch-based hard carbon negative electrode material, comprising the following steps:
[0076] S1. The asphalt is crushed by a mechanical crusher, and after screening, the crushed asphalt with a particle size of 5 μm is obtained, and then pre-oxidized for 5 hours at a temperature of 350° C. in an air atmosphere to obtain oxidized asphalt;
[0077] S2. After cooling the oxidized asphalt to room temperature, the asphalt was placed in a nitrogen atmosphere and subjected to high-temperature calcination and carbonization at 1200°C for 2 hours. After cooling, an asphalt-based hard carbon negative electrode material was obtained.
[0078] Comparative Example 2
[0079] This comparative example provides a method for preparing a modified asphalt-based hard carbon negative electrode material, comprising the following steps:
[0080] S1. The asphalt is crushed by a mechanical crusher, and after screening, the crushed asphalt with a particle size of 5 μm is obtained, and then pre-oxidized for 5 hours at a temperature of 350° C. in an air atmosphere to obtain oxidized asphalt;
[0081] S2. The oxidized asphalt was subjected to gas-phase coating treatment by fluidized bed CVD equipment, the oxidized asphalt was placed in a fluidized bed reactor, nitrogen was used as a carrier, methane was introduced into the fluidized bed reactor, and a hard carbon precursor material was deposited at a temperature of 800 ° C; wherein the amount of methane introduced was the same as the total amount of the carbon source gas and the organic gas introduced in Example 1;
[0082] S3. After the hard carbon precursor is cooled to room temperature, it is placed in a nitrogen atmosphere and subjected to high-temperature calcination and carbonization at 1200°C for 2 hours. After cooling, an amorphous carbon-coated modified asphalt-based hard carbon negative electrode material is obtained.
[0083] Performance Testing:
[0084] When the negative electrode materials prepared in Examples 1 to 9 and Comparative Examples 1 to 2 are used as negative electrode materials for sodium ion batteries, the electrode test conditions are:
[0085] The electrode is composed of 80% asphalt-based hard carbon negative electrode material and 20% other materials with a mass ratio of Super P:PVDF=1:1. The electrolyte is a solvent with a volume ratio of EC:DEC=1:1 and 1 mol sodium hexafluorophosphate dissolved in it. The separator is glass fiber, and the positive electrode is a sodium sheet. It is processed into a CR2032 button cell. The test conditions are: first discharge at a rate of 0.1C, then discharge at a constant current of 0.02mA, and then charge at a rate of 0.1C for testing.
[0086] The schematic diagram of the first charge and discharge of the modified asphalt-based hard carbon negative electrode material prepared in Example 1 is as follows: Figure 1 As shown;
[0087] The preparation parameters and performance data of the negative electrode materials prepared in each embodiment and comparative example are shown in Table 1:
[0088] Table 1
[0089]
[0090] It can be seen from Table 1 that by changing the preparation parameters of the modified asphalt-based hard carbon negative electrode material, the reversible capacity can reach 298mAh / h, and the first coulombic efficiency is increased to 88%; Comparing Example 1 and Comparative Example 1, the surface of the oxidized asphalt that has not been treated with vapor deposition coating does not present an amorphous carbon coating structure after high-temperature calcination and carbonization, and cannot further hinder the irreversible sodium adsorption phenomenon, so the electrochemical performance is poor; Comparing Example 1 and Comparative Example 2, the vapor deposition coating gas is completely replaced by an equal amount of methane (organic gas), and the coating effect is poor, and the uniformity of the amorphous carbon structure is worse than that of propylene; Using propylene as a carbon source to dope a trace amount of organic gas can further accelerate the carbon deposition rate, promote the uniformity of carbon deposition, and help to form a more uniform amorphous carbon coating layer, thereby improving the structural stability and conductivity of the material.
[0091] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0092] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a modified asphalt-based hard carbon negative electrode material, characterized in that: The following steps are involved: S1. The asphalt is crushed to obtain crushed asphalt, and pre-oxidized in an air atmosphere to obtain oxidized asphalt; S2. A gas-phase coating method is used to react a mixed gas composed of a carbon source gas and an organic gas with an oxidized asphalt to obtain a hard carbon precursor; S3. The hard carbon precursor is placed in an inert atmosphere for calcination and carbonization, and after cooling, a modified asphalt-based hard carbon negative electrode material is obtained.
2. The method for preparing a modified asphalt-based hard carbon negative electrode material according to claim 1, characterized in that: In S1, the asphalt includes any one of petroleum asphalt, coal asphalt, and natural asphalt, or a combination of several of them.
3. The method for preparing a modified asphalt-based hard carbon negative electrode material according to claim 1, characterized in that: In S1, the asphalt is crushed by a mechanical crusher. 50 3-10μm.
4. The method for preparing a modified asphalt-based hard carbon negative electrode material according to claim 1, characterized in that: In S1, the pre-oxidation temperature is 300-500° C., and the pre-oxidation time is 3-10 hours.
5. The method for preparing a modified asphalt-based hard carbon negative electrode material according to claim 1, characterized in that: In S2, the volume ratio of the carbon source gas to the organic gas is 6:(1-2).
6. The method for preparing a modified asphalt-based hard carbon negative electrode material according to claim 1, characterized in that: In S2, the organic gas is one or a mixture of two or more of methane, ethane and toluene.
7. The method for preparing a modified asphalt-based hard carbon negative electrode material according to claim 1, characterized in that: In S2, the mass ratio of the carbon source gas to the oxidized asphalt is (5-10):100; And / or, the carbon source gas is propylene.
8. The method for preparing a modified asphalt-based hard carbon negative electrode material according to claim 1, characterized in that: In the above S2, the coating temperature of the gas phase coating method is 700-900°C.
9. The method for preparing a modified asphalt-based hard carbon negative electrode material according to claim 1, characterized in that: In the step S3, the calcination temperature is 900-1500° C. and the calcination time is 2-5 hours.
10. A modified asphalt-based hard carbon negative electrode material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Bagasse-based sodium ion battery hard carbon negative electrode active material and preparation and application thereof
CN115744871A
Method for preparing pitch-based foam carbon
CN101927996A
Uniformly modified silicon monoxide negative electrode material and preparation method and application thereof
CN113258051A
Lithium ion battery silicon-carbon negative electrode material and preparation method and application thereof
CN116169255A
Silicon-carbon negative electrode material, preparation method thereof and lithium ion battery
CN116169256A
Cited By
Sodium-ion battery hard carbon negative electrode material and preparation method and application thereof
CN120964770A